Anticoagulation Therapy After Biologic Aortic Valve Replacement - Myllykangas Monna E; Kiviniemi Tuomas O; Gunn Jarmo M; Salomaa Veikko V; Pietilä Arto; Niiranen Teemu J; Aittokallio Jenni (FRONTIERS MEDIA SA, 2022)
Objectives: Thromboembolism prophylaxis after biologic aortic valve replacement (BAVR) is recommended for 3 months postoperatively. We examined the continuation of oral anticoagulation (OAC) treatment and its effect on the long-term prognosis after BAVR.
Methods: We used nation-wide register data from 4,079 individuals who underwent BAVR. We examined the association between warfarin and the non-vitamin K antagonist oral anticoagulant use with death, stroke and major bleeding in 2010 – 2016.
Results: The risk of stroke was higher (HR 2.39, 95% CI 1.62 – 3.53, p < 0.001) and the risk of death was lower (HR 0.79, 95% CI 0.65 – 0.96, p = 0.016) in OAC-users compared to individuals without OAC. We observed no significant associations between OAC use and bleeding risk.
Conclusion: OAC use after BAVR was associated with increased risk of stroke and decreased risk of death. These observational findings warrant validation in randomized controlled trials before any clinical conclusions can be drawn.